Growing old at own home: A study among pre-elderly adults in Peninsular Malaysia - Samsudin, Shamzaeffa; Abdullah, Norehan; Ismail, Nur Syakiran Akmal; Hassan, Kalthum; Ahmad Zakuan, Ummu Atiyah (2019)
The study of changes and choices of living arrangements among older persons has been a key element of demography and sociology of the family. While many studies focus on the elderly respondents in understanding this matter, our aim is to seek answers from the pre-elderly adults concerning their preferred oldage living arrangements and analyse the factors affecting the choice. A multistage sampling technique was used in selecting the respondents aged 40 to 59 years from Peninsular Malaysia. The total of 1,153 respondents were interviewed face-to-face using a structured questionnaire and it was found that 83.8% of the respondents prefer growing old in their own homes. From the probit model, it suggests that age and household size have negatively influenced the likelihood of the elderly to live in their own homes while being a male has the opposite effect. Those who are married or divorced, at work, earn more than RM15,000 a month and have formal education are more likely to prefer to grow old in their own homes as compared to other alternatives. Understand the choices of the pre-elderly groups are deemed vital for early intervention. A comprehensive support system is needed to endorse the popular choice of independent living at old age.